Catalytically active perrhenate based ionic liquids: a preliminary ecotoxicity and biodegradability assessment. (18th May 2015) - Thu, Ha Bui Thi; Markiewicz, Marta; Thöming, Jorg; Reich, Robert M.; Korinth, Valentina; Cokoja, Mirza; Kühn, Fritz E.; Stolte, Stefan
Abstract : Recently it was shown that water and air stable perrhenate based ionic liquids (ILs) are promising catalysts for oxidation reactions. Abstract : Recently it was shown that water and air stable perrhenate based ionic liquids (ILs) are promising catalysts for oxidation reactions. For a broader application and in the context of green chemistry it is important to study in addition to their technical performance also their potential impact on environment and human health. This paper presents the first account on (eco)toxicological and biodegradation data for a set of ammonium and imidazolium based ILs with perrhenate anions.